Box-Behnken technique based multi-parametric optimization of electrostatic spray coating in the manufacturing of thermoplastic composites. Issue 14 (26th October 2019) - Goud, Vijay; Ramasamy, Alagirusamy; Das, Apurba; Kalyanasundaram, Dinesh
ABSTRACT: An electrostatic spray coating process was designed and developed in-house for consistent deposition of polypropylene powder on continuously fed carbon tow to produce a matrix coated towpreg. The electrostatic spray coating process was optimized for fiber volume fraction using Box-Behnken experimental design. An empirical multi-parametric equation was obtained to define the relationship between the process parameters (electrostatic voltage at the gun, velocity of the carbon towpreg, and the distance between the tip of gun and the towpreg) through response surface methodology. Experimental verification of the model showed a validation of 93%. The velocity of the carbon towpreg was found to have a more profound effect on the output response of fiber volume fraction when compared to other process parameters.